Perlindungan Hukum Terhadap Konsumen Pembeli Makanan Berbuka Puasa yang Mengandung Bahan Pengawet dan Bahan Pemanis Buatan (Kajian UU No. 8 Tahun 1999) - Yaurwarin, Wahid (Public Policy, 2020)
Abstrak Law No. 8 of 1999 concerning consumer protection, in Article 1 paragraph 1 explains that consumer protection is any effort that guarantees legal certainty to provide protection to consumers. And one form of protection for consumers, in accordance with Law No. 8 of 1999 this form of Consumer Protection, is the protection of consumer safety in consuming food and drinks containing preservatives and artificial sweeteners. The purpose of this paper is the author wants to inform the public, especially consumers who usually buy food and drinks during the fasting month or friendly month and to break the fast, that there are legal regulations that protect their rights as consumers namely Law Number 8 of 1999. This research uses a normative juridical approach, based on statute (statute aproach), specifically Law Number 8 of 1999 concerning Consumer Protection, which is research focused on examining the application of rules or norms in positive law. The conclusion of this paper is that with the birth of Law No. 8 of 1999 concerning Consumer Protection, it is an attempt by the government to provide protection to consumers based on the existence of a number of consumer rights that need to be protected from actions that might be detrimental to other parties. These rights are fundamental and universal in nature so they need to get guarantees from the State for their fulfillment. Keywords: Legal Protection, Consumer Food Buyer